Dating Apps Front Stage and Back Stage: How Indonesian Represent Themselves on Tinder - Muhammad Farel Salahudin; Jo Ellaine Sumeisey; Indra Prawira (Syntax Corporation, 2022)
Tinder, which dominates the market in Western countries and targets mobile daters, has recently taken over the dating scene on a global scale. The development of the Internet has changed how we initiate and maintain interpersonal relationships. The dominance of dating apps is also evident in Southeast Asia, with nearly half of Indonesian respondents using dating apps. Dating apps profiles are how people introduce themselves to other people, and user-written profiles on dating apps enable users to represent themselves to potential matches on their own. Users may be compelled to provide information that they think will benefit them in using dating apps to achieve their goals. Using Erving Goffman's dramaturgy theory, this study aimed to look at the front stage and back stage of Indonesian Tinder user. By using convenience sampling to explore through the tinder profiles, 11 in-depth, semi-structured interviews and content analysis of Tinder profiles in Indonesia were conducted. The findings indicate that users might try to control the impression they create and can be seen through their photos, biographies, interests, and connected accounts. It can also provide information about their fashion and etiquette, while their bio can provide information on how they use languages. Most of the participants comply to Indonesian culture and beliefs when it comes to their profiles since it is more socially acceptable, and participants are consistent with their Tinder profiles and how they are behind the profiles.